Penilaian Mahasiswa BIPA terhadap Pembelajaran Tatap Muka dan Online - Defina Defina (Badan Pengembangan dan Pembinaan Bahasa, 2021)
The transition of face-to-face learning to online in a short time due to the Covid-19 pandemic is certainly not easy, both for teachers and for students. In this regard, the purpose of this paper is to explain 1) an overview of BIPA learning before and at the beginning of Covid-19; 2) learners' assessment of the ease, constraints of online learning, and their comparison with face-to-face; 3) learners' written opinion regarding online and face-to-face learning. This research is a qualitative descriptive design. Data were collected through observation and questionnaires. As a result, the form of face-to-face assignments consists of individuals, groups, and fields, whereas online is only individual assignments; the learning material is the same: grammar, 4 language skills, culture; PPSX, WA, e-mail learning tools. Learners experience problems in online learning. The learner has written advice in interactive learning and the use of English. Face-to-face learning is better than online learning.